SEEDLING EMERGENCE OF PRIMED AND UNPRIMED TOMATO SEEDS AT DIFFERENT TEMPERATURE LEVELS - Suena, Wayan (AGRICA, 2010)
The aim of this research is; to find out the response of the seed immersion treatment to the germination of tomato seeds at high and low-temperature levels. High-quality Joaquin and Roma seeds are judged by high genotype, low vigour and the appearance of sprouts determined every day until the sprouts have one pair of leaves that open perfectly. Sprouts have a pair of germination of leaves takes 12-19 days after the germination period. The results showed that the effect of the immersion treatment on the dry weight of the sprouts was most prominent in the immersion treatment at temperatures of 15 ° C and 30 ° C. The best sprouts grew significantly faster than the sprouts on the immersion treatment at 25 ° C as indicated by both genotypes.